2011
DOI: 10.1057/eps.2010.76
|View full text |Cite
|
Sign up to set email alerts
|

Online Discussion Forums

Abstract: It has been suggested that interaction in online learning programmes promotes student-centred learning, encourages wider student participation, and produces more in-depth and reasoned discussions than traditional face-to-face programmes (Karayan and Crowe (1997) and Smith and Hardaker (2000) cited in Davies and Graff (2005: 1)). In this article, the participation rates and usage patterns by undergraduate political science students of online discussion forums are examined. The study is guided by a number of que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The relationship between the use of discussion forums and academic performance has been studied previously (Buckley, 2011;Davies & Graff, 2005). However, some have suggested that forums could also increase student engagement (Bean, 2011;Brookfield & Preskill, 2005;Donnelly & Gardner, 2011), though this assertion has not been empirically examined.…”
Section: Discussion Forums and Student Engagementmentioning
confidence: 99%
“…The relationship between the use of discussion forums and academic performance has been studied previously (Buckley, 2011;Davies & Graff, 2005). However, some have suggested that forums could also increase student engagement (Bean, 2011;Brookfield & Preskill, 2005;Donnelly & Gardner, 2011), though this assertion has not been empirically examined.…”
Section: Discussion Forums and Student Engagementmentioning
confidence: 99%
“…Additionally, online discussions afford higher-order thinking. The delayed feature in discussion boards provides learners with extra time to reflect on written messages and conduct research before responding, which can result in more in-depth and reasoned responses (Buckley, 2011;Curry & Cook, 2014;Hew & Cheung, 2008;Klisc, McGill & Hobbs, 2012). Furthermore, online discussions can improve students' social skills, as they enable students to interact with others, e.g.…”
mentioning
confidence: 99%
“…There are three forms of interaction which are student-student interaction, student-instructor interaction, and student-content interaction (G. E. Moore, Warner, & Jones, 2016). These interactions can establish meaningful communication (Dixon, 2014), contribute to a greater sense of community (Buckley, 2011;Hammond, 2017;Moody, 2004), result in critical thinking and new knowledge construction (Chen, Chang, Ouyang, & Zhou, 2018;Williams & Lahman, 2011;Zhu, 2006), and lead to enhanced student engagement in online education (Dixson, 2010;G. E. Moore et al, 2016).…”
Section: Importance Of Online Discussionmentioning
confidence: 99%
“…E. Moore et al, 2016). Second, online discussion motivates students to have more in-depth discussion and compose more thoughtful responses than discussion in a traditional face-to-face class because students have more time to process and thoroughly think through the information (Buckley, 2011;Gao, Zhang, & Franklin, 2013;E. Lee & Hannafin, 2016).…”
Section: Importance Of Online Discussionmentioning
confidence: 99%
See 1 more Smart Citation